THE ROLE OF TECHNOLOGY IN MODERN CLASSROOMS - Quronboyeva Dinora Farxod kizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article explores the role of technology in modern classrooms, focusing on how digital tools influence the teaching and learning process. The study examines the main advantages of using technology, such as increased student engagement, access to a wide range of information, and the use of interactive teaching methods. It also considers the challenges associated with technology, including distractions, unequal access to devices, and overdependence on digital tools. The article highlights how technology supports collaboration, communication, and personalized learning experiences. Additionally, it discusses the importance of teachers’ digital competence and the need for a balanced approach when integrating technology into education. The findings suggest that while technology can greatly enhance learning, it must be used effectively and responsibly. The article concludes that technology plays a crucial role in improving the quality of education in modern classrooms.